Symbolic Literacy and Sharia Pseudo-Inclusion: A Paradoxical Analysis and TSR-Maqasid Strategy in Indonesia - Istianingsih, Istianingsih; Adiandari, Ade Maharini; Arafah, Willy; Doktoralina, Caturida Meiwanto; Nugroho, Lucky (Pelita : Jurnal Penelitian, Terapan dan Aplikatif, 2025)
This research is motivated by the phenomenon of a significant gap between the literacy index and Islamic financial inclusion in Indonesia, as well as the fraud case of PT Dana Sharia Indonesia (DSI) in 2026 which reveals the practice of "pseudo-inclusion". This study aims to identify the determinants of literacy and formulate an integrative strategy to overcome this paradox through the framework  of Tawhid String Relationship (TSR) and Maqasid Syariah. The method used is descriptive qualitative with a literature study approach using data from the 2025 National Survey of Financial Literacy and Inclusion (SNLIK) and the Indonesia Sharia Economic Outlook (ISEO) 2024 report. The results of the study show that literacy is still "symbolic", where people know the term sharia but do not understand the risks of contracts, thus triggering financial vulnerability. The solution strategy includes contract-based education synergy, algorithmic ethics audits in financial technology, and regulatory strengthening. The implications of the study emphasize the need to transform education from cognitive to applicative to protect property (Hifz al-Mal) and reason (Hifz al-Aql). The novelty of this research lies in an in-depth analysis of the 2026 DSI default case and the use of the latest SNLIK 2025 data.